Fashion design workshop - Corfee, Stephanie, 1974- (WF studio., 2011)
"This delightful guide offers budding artists the perfect introduction to the fundamentals of fashion figure drawing. Showcasing the hip, girly artistic style of Stephanie Corfee, the step-by-step projects cover a range of looks--from sophisticated and elegant to cool and casual."--Amazon.com.